Seaweed iodized salt and preparation method thereof
By using specific enzymes and buffers for ultrasonic treatment in the preparation of seaweed iodine salt, combined with anion separation column and ceramic membrane filtration technology, the problem of difficulty in extracting organic iodine in seaweed iodine salt and poor stability in inorganic iodine is solved, and seaweed iodine salt products with high content and low heavy metals are achieved, meeting the national edible salt standards.
Patent Information
- Application Number
- CN202411618529.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-11-13
AI Technical Summary
In the prior art, organic iodine of seaweed iodine is difficult to extract, inorganic iodine is poor, and heavy metals are difficult to completely remove during the extraction process, affecting the stability and pass rate of the product.
Seaweed substances are treated under ultrasonic conditions using specific enzymes and buffers, combined with specific anion separation columns and ceramic membrane filtration technology, seaweed iodine crystals are extracted and separated, and the pH value is adjusted through ammonium ferric citrate to enhance product stability.
It improves the iodine content and purity of seaweed iodine crystals, ensures the stability of inorganic iodine, reduces the heavy metal content, meets the national standards for edible salt, and has good edible value.
Smart Images

Figure BDA0005132875760000131
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of salt manufacturing, and in particular relates to seaweed iodized salt and a preparation method thereof. Background Art
[0002] Seaweed iodized salt is a new generation of iodized salt made from natural biological seaweed and scientifically processed. It not only contains inorganic iodine that is easily absorbed by the human body, but is also rich in organic iodine. It is an ideal natural seasoning iodine supplement. Moreover, iodinated amino acids such as monoiodotyrosine and 3.5-diiodotyrosine in organic iodine are not only easily absorbed by the human body, but iodinated amino acids may also protect the myocardium by increasing the activity of ATPase. Organic iodine containing iodinated amino acids at higher doses is safer and more reliable than inorganic iodine. Therefore, compared with some inorganic iodized salts, seaweed iodized salt will not cause adverse reactions such as hyperiodinated goiter when the dose is slightly excessive.
[0003] However, in the prior art, although organic iodine in seaweed is more convenient for storage and utilization, it is difficult to extract, and although inorganic iodine is easily absorbed by the human body, it has poor stability and is prone to redox reactions to generate elemental iodine that sublimates, affecting the stability of seaweed iodized salt. In addition, the extraction method of seaweed iodine is relatively complicated, and it is difficult to completely remove heavy metals in seaweed substances during the extraction process, affecting the product qualification rate. Summary of the invention
[0004] The purpose of the present invention is to provide a seaweed iodized salt and a preparation method thereof. The seaweed iodized salt not only has an iodine content that meets national standards, but also has a high organic iodine content and good inorganic iodine stability. At the same time, the heavy metal content is low, the national edible salt requirements are met, and the salt has good edible value.
[0005] The invention discloses iodized seaweed salt, wherein the raw materials for preparing the seaweed salt include, by weight, 100-150 parts of iodine-free salt, 0.1-0.5 parts of seaweed iodine crystals, and an appropriate amount of ammonium ferric citrate.
[0006] The preparation method of seaweed iodine crystals comprises the following steps:
[0007] S1, washing the seaweed material with deionized water for 2 to 3 times, drying and crushing at 50 to 70° C. and passing through a 40-mesh sieve to obtain seaweed powder;
[0008] S2, mixing seaweed powder with buffer, stirring evenly and adjusting the pH to 7-8, adding enzyme, ultrasonic treatment and centrifugation, vacuum filtration to obtain filtrate, repeating the above operation on the residue, combining the filtrate, decompressing and concentrating the filtrate to dryness, and obtaining a crude seaweed extract;
[0009] S3. Dissolve the crude seaweed extract in water, pass it through an anion separation column at a flow rate of 2.5-3.5 BV / h, and use the mobile phase for step-by-step elution for 40-70 min. Collect the eluate, let it stand for 20-30 h, then filter it with a ceramic membrane, collect the filtrate, and concentrate and dry it under reduced pressure to obtain seaweed iodine crystals.
[0010] Preferably, the seaweed material is one or more of Nostoc, Porphyra, Laminaria, Sea Cabbage and Undaria; further preferably, it is Laminaria.
[0011] Preferably, the solid-liquid ratio of the seaweed powder and the buffer solution is 1 g: 15-25 mL.
[0012] Preferably, the buffer solution is NaH2PO4 solution.
[0013] Preferably, the concentration of NaH2PO4 in the buffer solution is 0.1 to 0.2 mol / L.
[0014] Preferably, the added amount of the enzyme is 0.2% to 0.5% of the seaweed powder; more preferably, it is 0.4%.
[0015] Preferably, the enzyme is trypsin and a complex protease.
[0016] Preferably, the mass ratio of trypsin to composite protease is (2-4):1; more preferably, it is 3:1.
[0017] Preferably, the trypsin has an enzymatic activity of ≥15000 U / g.
[0018] In some preferred embodiments, the trypsin is purchased from Hunan Yunbang Pharmaceutical Co., Ltd.
[0019] Preferably, the enzyme activity of the composite protease is ≥40000 U / g.
[0020] In some preferred embodiments, the composite protease is purchased from Shandong Aicai Biotechnology Co., Ltd.
[0021] The specific conditions of the ultrasonic treatment are: ultrasonic power of 100-150W, ultrasonic time of 8-12h, and ultrasonic temperature of 45-55°C.
[0022] The inventors found that the iodine content in seaweed iodine crystals can be increased by using specific enzymes and buffers to treat seaweed materials under ultrasonic conditions. This may be because inorganic iodine can be leached from the seaweed matrix under specific buffer solutions and ultrasonic treatment conditions, and ultrasonic treatment combined with enzymes can accelerate the rupture of plant cell walls, reduce the transfer resistance of active ingredients, and promote the extraction and separation of organic iodine. The combination of the two significantly increases the iodine content. Specific ultrasonic conditions and specific enzymes work synergistically, on the one hand, increasing enzyme catalytic activity, helping to destroy plant cell walls and reduce the mass transfer resistance of organic iodine; on the other hand, increasing the solubility and diffusion coefficient of organic iodine, which is beneficial to the extraction of organic iodine. However, in the actual preparation process, it is necessary to control the conditions, and a long ultrasonic treatment time may cause the decomposition of iodine amino acids and the loss of potassium iodide. Excessive temperature will affect enzyme activity on the one hand, and on the other hand, it will also affect the stability of inorganic iodine, thereby reducing the iodine extraction rate. If the amount of enzyme added is too high, the cell wall of seaweed materials will be broken more thoroughly. At this time, in addition to leaching iodine, the buffer will also dissolve too many impurities, affecting the purity and stability of the product.
[0023] Preferably, the solid-liquid ratio of the crude seaweed extract and water is 1 g: 10-20 mL.
[0024] Preferably, the bonded phase of the anion separation column is quaternary ammonium, the particle size is 4 to 6 μm, and the number of theoretical plates of a chromatographic column is ≥10,000.
[0025] In some preferred embodiments, the anion separation column is purchased from Lisenok Scientific Instruments (Shanghai) Co., Ltd., Shodex IC S I-504E.
[0026] The inventors found that by selecting a specific anion separation column, the iodine separation efficiency can be improved, thereby increasing the iodine content in the seaweed iodine crystals. This may be because, on the one hand, the quaternary ammonium group not only has a strong ion exchange capacity, which can effectively adsorb iodine ions, thereby improving its separation efficiency and selectivity, but also has high chemical stability, which can ensure stable separation. On the other hand, selecting a separation column with a specific particle size can increase its contact area with the solution, thereby increasing the amount of iodine adsorbed.
[0027] Preferably, the mobile phase is (NH4)2CO3 / NaOH solution.
[0028] Preferably, the concentration of (NH4)2CO3 in the mobile phase is 0.01 to 0.02 mol / L.
[0029] Preferably, the pH of the mobile phase is 8-10.
[0030] Preferably, the specific steps of the stepwise elution are: the flow rate of the mobile phase is 0.6-1.0 mL / min before 20-30 min, and the flow rate is 1.1-1.3 mL / min thereafter.
[0031] In some preferred schemes, a specific eluent is configured to further improve the collection rate of organic iodine, thereby increasing the content of iodine amino acids in seaweed iodized salt. This may be because ammonium carbonate will dissociate into carbonate ions or bicarbonate ions at a specific pH, and these ions can compete with the anions of organic iodine and inorganic iodine adsorbed on the anion separation column to exchange, thereby replacing iodine ions from the resin and flowing out with the eluent. Due to the dissociation characteristics of ammonium carbonate and the exchange capacity with the resin, it can effectively elute the iodine ions adsorbed on the resin. The inventor has found through a large number of experiments that the selection of a specific mobile phase concentration and pH can increase the elution amount of organic iodine. This may be because in a specific mobile phase solution, organic iodine can not only be completely separated from the anion separation column, but also can be retained in the mobile phase solution for a long time. However, an excessively high concentration of ammonium carbonate will not only reduce the retention time of iodine amino acids, but also easily produce sediments on the separation column, causing it to be blocked or corroded, thereby affecting the separation effect of the anion separation column. In addition, during the elution process. The flow rate of the mobile phase also has a great influence on the separation degree of iodine ions. When the flow rate is low, the retention time of iodine ions will be delayed, and the separation time is too long, resulting in some iodine ions being unable to be eluted, while when the flow rate is too high, the separation degree may be reduced, and the high flow rate causes the column pressure to be too high, shortening the service life of the anion exchange column. The inventors have found that by using the step-by-step elution method, it is possible to shorten the separation time while separating inorganic iodine and organic iodine, while reducing the damage to the anion exchange column, thereby avoiding the impact of the iodine separation amount due to the damage of the anion exchange column during industrial use.
[0032] Preferably, the transmembrane pressure difference during the filtration in step S3 is 0.05 to 0.15 MPa.
[0033] The method for preparing the modified ceramic membrane comprises the following steps:
[0034] B1. Take a silane coupling agent and hydrolyze it in an ethanol aqueous solution with a concentration of 80wt% and heat it to 55-65°C. After immersing the ceramic membrane in the solution for 2-4 hours, rinse it with deionized water and dry it at 100-120°C for 3-5 hours to obtain a silane coupling agent modified ceramic membrane;
[0035] B2. Prepare polyvinyl alcohol into a polyvinyl alcohol aqueous solution with a mass concentration of 0.5% to 2%, add graphene oxide thereto and disperse evenly to obtain a mixed solution, use a vacuum migration method to completely immerse the silane coupling agent modified ceramic membrane in the mixed solution, vacuum treat for 20 to 30 minutes, then take it out, and heat treat it at 100 to 200° C. for 1 to 3 hours to obtain the obtained product.
[0036] In some preferred schemes, the eluent is filtered with a ceramic membrane, and suspended solids, colloids, bacteria, viruses, etc. larger than the membrane pore size will be trapped on one side of the membrane, thereby ensuring the purity and stability of the seaweed iodine crystals, and the ceramic membrane filtration process is gentle, no harmful chemicals are introduced, and the activity of iodine in the seaweed iodine crystals can be maintained to the maximum extent, reducing its degradation and loss during the extraction process. However, the filtration time is long, and some impurities may block the holes, resulting in limited purification effects, and the heavy metals in the seaweed substances cannot be removed. The inventors found that constructing a layer of new graphene oxide film on the surface of the ceramic membrane can improve the stability of the modified ceramic membrane while also improving the adsorption of heavy metals in the eluent, thereby improving the purity of the prepared seaweed iodine crystals, making its heavy metal content lower than the national standard. This may be because graphene oxide has a large specific surface area and abundant adsorption sites, and contains active functional groups such as hydroxyl and carboxyl groups, so it can effectively adsorb heavy metal ions, organic pollutants, etc. in water. In addition, the layered structure of graphene oxide also provides it with more adsorption space, making its adsorption capacity relatively large. This greatly improves the purity of the final seaweed iodine, but the adhesion effect between graphene oxide and the ceramic membrane is poor.
[0037] Preferably, the volume ratio of the silane coupling agent to the ethanol aqueous solution is 1:30-50; more preferably, it is 1:40.
[0038] Preferably, the silane coupling agent is 3-aminopropyltrimethoxysilane and γ-mercaptopropyltrimethoxysilane.
[0039] Preferably, the mass ratio of 3-aminopropyltrimethoxysilane to γ-mercaptopropyltrimethoxysilane is 1:(5-7); further preferably, it is 1:6.
[0040] The inventors discovered through a large number of experiments that by selecting two silane coupling agents to modify the ceramic membrane, amino, thiol and other functional groups were grafted onto the surface of the ceramic membrane, which can react with the epoxy groups on the graphene oxide, so that the graphene oxide can adhere to the ceramic membrane, thereby improving the adsorption effect of the ceramic membrane; at the same time, by controlling the particle size and other properties of the ceramic membrane and graphene oxide, the prepared modified ceramic membrane can be used for precision filtration, further improving the purity of the final seaweed iodine crystals.
[0041] Preferably, the separation pore size of the ceramic membrane is 0.4-0.5 μm, the material is Al2O3-ZrO2, and it is purchased from Beijing Dopson Membrane Application Engineering Technology Co., Ltd.
[0042] Preferably, the alcoholysis degree of the polyvinyl alcohol is ≥99%, the ash content is ≤0.5%, and the viscosity of the polyvinyl alcohol prepared into a 4 wt % aqueous solution is 15-25 CP.
[0043] In some preferred embodiments, the polyvinyl alcohol is purchased from Japan Kuraray polyvinyl alcohol 80-18.
[0044] Preferably, the graphene oxide includes single-layer graphene oxide and multi-layer graphene oxide.
[0045] Preferably, the weight ratio of the single-layer graphene oxide to the multi-layer graphene oxide is 1:(0.5-2); further preferably, it is 1:1.
[0046] Preferably, the average thickness of the single-layer graphene oxide is 0.5 to 1.2 nm, and the diameter is 4 to 7 μm.
[0047] Preferably, the multilayer graphene oxide has an average thickness of 1 to 3 nm, a diameter of 4 to 7 μm, and 2 to 5 layers.
[0048] In some preferred embodiments, the single-layer graphene oxide and the multi-layer graphene oxide are both purchased from Zhejiang Zhiti Nano Micro New Materials Co., Ltd.
[0049] Preferably, the solid-to-liquid ratio of the graphene oxide to the polyvinyl alcohol aqueous solution is 1-10 g:100 mL.
[0050] In order to improve the filtering effect and stability of the ceramic membrane, two specific graphene oxides are selected to modify it. This may be because on the one hand, specific single-layer graphene oxide and multi-layer graphene oxide are selected, which have similar diameters and little difference in thickness, so there is a certain compatibility between the two. On the one hand, the complementarity in the number of layers is achieved, which not only retains the high activity of the single-layer graphene oxide, but also improves the mechanical properties of the product. On the other hand, the single-layer and multi-layer graphene oxides of similar size are intertwined and stacked to form a stable three-dimensional network structure, which can improve the structural stability of the modified ceramic membrane. In addition, the additive liquid of specific polyvinyl alcohol can improve the adhesion of the ceramic membrane matrix and graphene oxide, thereby also improving the structural stability of the modified ceramic membrane. However, considering the agglomeration effect of graphene oxide, its addition amount should not be too much, and excessive agglomerated graphene oxide loaded on the surface of the ceramic membrane may block the ceramic pores and affect the filtering effect.
[0051] The preparation method of seaweed iodized salt comprises the following steps: dissolving seaweed iodized crystals in water and stirring evenly, adding ammonium ferric citrate, continuing stirring, adding baking soda to adjust the pH value of the solution to 7-9, adding the solution to iodine-free salt, stirring evenly and drying to obtain seaweed iodized salt.
[0052] Preferably, the solid-liquid ratio of seaweed iodine to water is 1 g: 100-150 mL.
[0053] Preferably, the added amount of the ammonium ferric citrate does not exceed 0.0025% of the total mass of the iodine-free salt and the seaweed iodine crystals.
[0054] Preferably, the pH of the baking soda solution is adjusted to 8-9.
[0055] The inventors found that in the process of preparing seaweed iodized salt, after seaweed iodized crystals and ammonium ferric citrate are mixed by weight, the pH is adjusted to a specific value, which can enhance the stability of seaweed iodized salt while ensuring the anti-caking effect of ammonium ferric citrate. This may be because under specific pH conditions, the trivalent iron in ammonium ferric citrate will not generate ferric hydroxide, and inorganic iodine, trivalent iron and oxygen will not undergo oxidation and reduction to cause the precipitation of elemental iodine, thereby greatly ensuring the stability of the system and enhancing the stability of inorganic iodine. At the same time, ammonium ferric citrate can exert its anti-caking effect, and other properties of seaweed iodized salt will not be affected, and it has excellent stability.
[0056] Compared with the prior art, the advantages and beneficial effects of the present invention are:
[0057] 1. The present invention provides a seaweed iodized salt, which has a high organic iodine content, good inorganic iodine stability, and a low heavy metal content, meets national edible salt requirements, and has good edible value.
[0058] 2. The present invention uses specific enzymes and buffer to treat seaweed materials under ultrasonic conditions, which can increase the iodine content in seaweed iodine crystals.
[0059] 3. The present invention can improve the iodine separation efficiency by selecting a specific anion separation column, thereby increasing the iodine content in the seaweed iodine crystals.
[0060] 4. The present invention can further improve the collection rate of organic iodine by selecting a specific eluent, thereby increasing the content of iodine amino acids in seaweed iodized salt.
[0061] 5. The present invention can increase the elution amount of organic iodine by selecting a specific mobile phase concentration and pH.
[0062] 6. The present invention constructs a new graphene oxide film on the surface of the ceramic membrane, which can improve the stability of the modified ceramic membrane and increase the adsorption of heavy metals in the eluent, thereby improving the purity of the prepared seaweed iodine crystals and making its heavy metal content lower than the national standard. DETAILED DESCRIPTION
[0063] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0064] The raw materials used in the present invention are all commercially available, specifically:
[0065] Trypsin with an enzymatic activity of about 20,000 U / g was purchased from Hunan Yunbang Pharmaceutical Co., Ltd.
[0066] The enzyme activity of the composite protease was about 50,000 U / g and was purchased from Shandong Aicai Biotechnology Co., Ltd.
[0067] The bonded phase of the anion separation column was quaternary ammonium, the particle size was 5 μm, the theoretical plate number of one chromatographic column was ≥10,000, and it was purchased from Lisenok Scientific Instruments (Shanghai) Co., Ltd., Shodex ICS I-504E.
[0068] The separation pore size of the ceramic membrane is 0.45 μm, and the material is Al2O3-ZrO2, which was purchased from Beijing Dopson Membrane Application Engineering Technology Co., Ltd.
[0069] The alcoholysis degree of polyvinyl alcohol is ≥99%, the ash content is ≤0.5%, and the viscosity of the polyvinyl alcohol prepared into a 4wt% aqueous solution is 15-25CP. The polyvinyl alcohol is purchased from Kuraray Polyvinyl Alcohol 80-18 of Japan.
[0070] The average thickness of single-layer graphene oxide is 0.5-1.2 nm, and the diameter is 4-7 μm; the average thickness of multi-layer graphene oxide is 1-3 nm, the diameter is 4-7 μm, and the number of layers is 2-5; all are purchased from Zhejiang Zhiti Nano Micro New Materials Co., Ltd.
[0071] Example 1
[0072] The present embodiment provides a seaweed iodized salt, and the raw materials for its preparation are, by weight: 120 parts of iodine-free salt, 0.3 parts of seaweed iodized crystals, and an appropriate amount of ammonium ferric citrate.
[0073] The preparation method of seaweed iodine crystals comprises the following steps:
[0074] S1, washing the seaweed material with deionized water for three times, drying and crushing at 60°C and passing through a 40-mesh sieve to obtain seaweed powder;
[0075] S2, mixing seaweed powder with buffer, stirring evenly and adjusting the pH to 8, adding enzyme, ultrasonically treating and centrifuging, vacuum filtering to obtain filtrate, repeating the above operation with the residue, combining the filtrate, decompressing and concentrating the filtrate to dryness, and obtaining a crude seaweed extract;
[0076] S3. Dissolve the crude seaweed extract in water, pass it through an anion separation column at a flow rate of 3BV / h, and use the mobile phase for step-by-step elution for 60 minutes. Collect the eluate, let it stand for 25 hours, filter it with a ceramic membrane, collect the filtrate, and concentrate and dry it under reduced pressure to obtain seaweed iodine crystals.
[0077] The seaweed material is kelp.
[0078] The solid-to-liquid ratio of the seaweed powder to the buffer solution is 1 g:20 mL.
[0079] The buffer solution is NaH2PO4 solution.
[0080] The concentration of NaH2PO4 in the buffer solution is 0.15 mol / L.
[0081] The added amount of the enzyme is 0.4% of the mass of the seaweed powder.
[0082] The enzymes are trypsin and complex protease.
[0083] The mass ratio of trypsin to compound protease is 3:1.
[0084] The specific conditions of the ultrasonic treatment are: ultrasonic power of 120W, ultrasonic time of 10h, and ultrasonic temperature of 50°C.
[0085] The solid-to-liquid ratio of the seaweed crude extract and water is 1 g:15 mL.
[0086] The mobile phase is (NH4)2CO3 / NaOH solution.
[0087] The concentration of (NH4)2CO3 in the mobile phase is 0.015 mol / L.
[0088] The pH of the mobile phase was 9.
[0089] The specific steps of the step-by-step elution are: the flow rate of the mobile phase is 0.8 mL / min before 25 min, and the flow rate is 1.2 mL / min thereafter.
[0090] The transmembrane pressure difference during the filtration in step S3 is 0.1 MPa.
[0091] The method for preparing the modified ceramic membrane comprises the following steps:
[0092] B1. The silane coupling agent is hydrolyzed in an ethanol aqueous solution with a concentration of 80 wt % and heated to 60° C. The ceramic membrane is immersed in the solution for 3 hours, then rinsed with deionized water and dried at 110° C. for 4 hours to obtain a silane coupling agent modified ceramic membrane;
[0093] B2. Prepare polyvinyl alcohol into a polyvinyl alcohol aqueous solution with a mass concentration of 1%, add graphene oxide thereto and disperse evenly to obtain a mixed solution, use a vacuum migration method to completely immerse the silane coupling agent modified ceramic membrane in the mixed solution, vacuum treat for 25 minutes, then take it out, and heat treat it at 150°C for 2 hours to obtain the product.
[0094] The volume ratio of the silane coupling agent to the ethanol aqueous solution is 1:40.
[0095] The silane coupling agent is 3-aminopropyltrimethoxysilane and γ-mercaptopropyltrimethoxysilane.
[0096] The mass ratio of the 3-aminopropyltrimethoxysilane to the γ-mercaptopropyltrimethoxysilane is 1:6.
[0097] The graphene oxide is single-layer graphene oxide and multi-layer graphene oxide.
[0098] The weight ratio of the single-layer graphene oxide to the multi-layer graphene oxide is 1:1.
[0099] The solid-to-liquid ratio of the graphene oxide to the polyvinyl alcohol aqueous solution is 1 g:20 mL.
[0100] The preparation method of seaweed iodized salt comprises the following steps: dissolving seaweed iodized crystals in water and stirring evenly, adding ammonium ferric citrate, continuing stirring, adding baking soda to adjust the pH value of the solution to 8.5, adding the solution to iodine-free salt, stirring evenly and drying to obtain the seaweed iodized salt.
[0101] The solid-liquid ratio of the seaweed iodine to water is 1g:120mL.
[0102] The added amount of the ammonium ferric citrate is 0.002% of the total mass of the iodine-free salt and the seaweed iodine crystals.
[0103] Example 2
[0104] The difference between this embodiment and embodiment 1 is that the mass ratio of trypsin to compound protease is 4:1.
[0105] Example 3
[0106] The difference between this embodiment and embodiment 1 is that the specific steps of the step-by-step elution are: the flow rate of the mobile phase is 0.6 mL / min before 20 min, and the flow rate is 1.3 mL / min thereafter.
[0107] Comparative Example 1
[0108] The difference between this comparative example and Example 1 is that the enzyme is trypsin.
[0109] Comparative Example 2
[0110] The difference between this comparative example and Example 1 is that the specific conditions of the ultrasonic treatment are: ultrasonic power is 120W, ultrasonic time is 15h, and ultrasonic temperature is 50°C.
[0111] Comparative Example 3
[0112] The difference between this comparative example and Example 1 is that the added amount of the enzyme is 1% of the seaweed powder.
[0113] Comparative Example 4
[0114] The difference between this comparative example and Example 1 is that the bonded phase of the anion separation column is quaternary ammonium, the particle size is 9 μm, the theoretical plate number of a chromatographic column is ≥5000, and it is purchased from Lisenok Scientific Instruments (Shanghai) Co., Ltd., Shodex ICS I-904E.
[0115] Comparative Example 5
[0116] The difference between this comparative example and Example 1 is: S3, take the seaweed crude extract and dissolve it in water, pass it through the anion separation column at a flow rate of 3BV / h, use the mobile phase to elute at a flow rate of 1.0mL / min for 60min, collect the eluate, let it stand for 25h, filter it with a ceramic membrane, collect the filtrate, concentrate and dry it under reduced pressure to obtain seaweed iodine crystals.
[0117] Comparative Example 6
[0118] The difference between this comparative example and Example 1 is that the separation pore size of the ceramic membrane is 0.9 μm, and the material is Al2O3-ZrO2, which is purchased from Beijing Dopson Membrane Application Engineering Technology Co., Ltd.
[0119] Comparative Example 7
[0120] The difference between this comparative example and Example 1 is that the silane coupling agent is 3-aminopropyltrimethoxysilane
[0121] Comparative Example 8
[0122] The difference between this comparative example and Example 1 is that the graphene oxide is a single-layer graphene oxide.
[0123] Comparative Example 9
[0124] The difference between this comparative example and Example 1 is that the preparation method of the seaweed iodized salt comprises the following steps: dissolving seaweed iodized crystals in water and stirring evenly, adding ammonium ferric citrate, continuing stirring, adding baking soda to adjust the pH of the solution to 10, adding iodine-free salt, stirring evenly, drying and concentrating, and obtaining seaweed iodized salt.
[0125] Performance Testing
[0126] The iodine content and Pb content in seaweed iodine crystals were tested with reference to GB 1903.39-2018 "National Food Safety Standard Food Nutrition Fortifier Seaweed Iodine". The percentage of organic iodine in seaweed iodine crystals to total iodine was tested with reference to the method in the paper "Research on Organic Iodine in Seaweed II: Existence Form and Content" by Han Lijun et al. The seaweed iodine salt was placed at 200°C for 1 hour and a thermal stability test was conducted. After the test, the iodine content was tested. The iodine loss rate = (initial iodine content - iodine content after thermal stability test) / initial iodine content × 100%. The results are shown in Table 1.
[0127] Table 1 Measurement results
[0128]
[0129] According to statistics, the iodine content and Pb content of the seaweed iodine crystals prepared in Examples 1 to 3 of the present invention meet national standards, and the proportion of organic iodine is relatively high, the iodine loss rate of the prepared seaweed iodized salt is low, and it has excellent stability. Comparative Example 1 does not add composite protease, Comparative Example 2 has a long ultrasonic treatment time, Comparative Example 3 adds too much enzyme, Comparative Example 4 has anion separation column particle size that is too high, the theoretical plate number is low, Comparative Example 5 does not perform step-by-step elution, Comparative Example 6 has a ceramic membrane separation pore size that is too high, Comparative Example 7 does not add γ-mercaptopropyltrimethoxysilane, Comparative Example 8 does not add multilayer graphene oxide, Comparative Example 9 has a high pH value of seaweed iodized salt, and the iodine content and organic iodine content of the prepared seaweed iodine crystals are both low, but the Pb content is too high, and the iodine loss rate of the prepared seaweed iodized salt at high temperature is too high. Therefore, the iodine content in the seaweed iodine crystals prepared by the raw materials and methods described in this application meets the national requirements, the organic iodine content is high, the stability of inorganic iodine is also good, and the heavy metal content is low, which meets the national edible salt requirements and has good edible value.
[0130] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A seaweed iodized salt, characterized in that: The raw materials for its preparation include 100-150 parts of iodine-free salt, 0.1-0.5 parts of seaweed iodine crystals, and an appropriate amount of ammonium ferric citrate; The preparation method of seaweed iodine crystals comprises the following steps: S1, washing the seaweed material with deionized water for 2 to 3 times, drying and crushing at 50 to 70° C. and passing through a 40-mesh sieve to obtain seaweed powder; S2, mixing seaweed powder with buffer, stirring evenly and adjusting the pH to 7-8, adding enzyme, ultrasonic treatment and centrifugation, vacuum filtration to obtain filtrate, repeating the above operation on the residue, combining the filtrate, decompressing and concentrating the filtrate to dryness, and obtaining a crude seaweed extract; S3, dissolving the seaweed crude extract in water, passing it through an anion separation column at a flow rate of 2.5-3.5 BV / h, eluting it step by step with a mobile phase for 40-70 min, collecting the eluate, filtering it with a ceramic membrane after standing for 20-30 h, collecting the filtrate, concentrating it under reduced pressure and drying it, to obtain seaweed iodine crystals; The added amount of the enzyme is 0.2% to 0.5% of the seaweed powder; the enzymes are trypsin and composite protease; the mass ratio of the trypsin and composite protease is (2 to 4): 1; the enzyme activity of the trypsin is ≥15000U / g; the enzyme activity of the composite protease is ≥40000U / g.
2. The seaweed iodized salt according to claim 1, characterized in that The buffer solution is a NaH2PO4 solution; the concentration of NaH2PO4 in the buffer solution is 0.1-0.2 mol / L.
3. The seaweed iodized salt according to claim 1, characterized in that The specific conditions of the ultrasonic treatment are: ultrasonic power of 100-150W, ultrasonic time of 8-12h, and ultrasonic temperature of 45-55°C.
4. The seaweed iodized salt according to claim 1, characterized in that The bonded phase of the anion separation column is quaternary ammonium, the particle size is 4-6 μm, and the theoretical plate number of a chromatographic column is ≥10,000.
5. The seaweed iodized salt according to claim 1, characterized in that: The mobile phase is (NH4)2CO3 / NaOH solution; the concentration of (NH4)2CO3 in the mobile phase is 0.01-0.02 mol / L; and the pH of the mobile phase is 8-10.
6. The seaweed iodized salt according to claim 1, characterized in that: The specific steps of the stepwise elution are: the flow rate of the mobile phase is 0.6-1.0 mL / min before 20-30 minutes, and the flow rate is 1.1-1.3 mL / min thereafter.
7. The iodized seaweed salt according to any one of claims 1 to 6, characterized in that: The method for preparing the modified ceramic membrane comprises the following steps: B1. Take a silane coupling agent and hydrolyze it in an ethanol aqueous solution with a concentration of 80wt% and heat it to 55-65°C. After immersing the ceramic membrane in the solution for 2-4 hours, rinse it with deionized water and dry it at 100-120°C for 3-5 hours to obtain a silane coupling agent modified ceramic membrane; B2. Prepare polyvinyl alcohol into a polyvinyl alcohol aqueous solution with a mass concentration of 0.5% to 2%, add graphene oxide thereto and disperse evenly to obtain a mixed solution, use a vacuum migration method to completely immerse the silane coupling agent modified ceramic membrane in the mixed solution, vacuum treat for 20 to 30 minutes, then take it out, and heat treat it at 100 to 200° C. for 1 to 3 hours to obtain the obtained product.
8. The seaweed iodized salt according to claim 7, characterized in that: The silane coupling agent is 3-aminopropyltrimethoxysilane and γ-mercaptopropyltrimethoxysilane.
9. The method for preparing iodized seaweed salt according to claim 8, characterized in that: The separation pore size of the ceramic membrane is 0.4-0.5 μm, and the material is Al2O3-ZrO2.
10. A method for preparing seaweed iodized salt according to any one of claims 1 to 9, characterized in that: The steps are: dissolving seaweed iodine crystals in water and stirring evenly, adding ammonium ferric citrate, continuing stirring, adding baking soda to adjust the solution pH to 7-9, adding to iodine-free salt, stirring evenly and drying to obtain seaweed iodized salt.
Citation Information
Patent Citations
Graphene oxide-based composite membrane for treating radioactive wastewater
CN105664738A
Preparation method and application of seaweed organic iodine powder and seaweed organic iodine salt
CN107080223A
Preparation and detection method of anti-caking green algae iodized salt
CN114287606A
Method for extracting iodine from seaweed
CN114807242A
Preparation method of graphene oxide self-assembled composite ceramic filter element
CN118491475A